2022
DOI: 10.3390/su142316262
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Research and Developments in the Low-Toxic Chelating Reagents for the Extraction of Non-Ferrous and Noble Metals from Poor Polymetallic Ores and Processing Tailings

Abstract: An urgent technological, economic and environmental task of mining and metallurgical enterprises is to involve poor, off-balance and hard-to-beneficiate ores in the technological process, as well as accumulated and current waste from mining and metallurgical industries. As the reserves of developed deposits are depleted, technogenic objects may become a priority, and in some cases the only, source of mineral raw materials. Mining wastes represent a large reserve of raw materials for the extraction of non-ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The use of a new reagent-a pyrazolone derivative-in combination with potassium butyl xanthate in the process of the flotation beneficiation of copper-zinc sulfide ores enables an increased recovery and content of copper and zinc in the concentrates of both copper and zinc flotations [13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a new reagent-a pyrazolone derivative-in combination with potassium butyl xanthate in the process of the flotation beneficiation of copper-zinc sulfide ores enables an increased recovery and content of copper and zinc in the concentrates of both copper and zinc flotations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Further laboratory and pilot tests showed that the best results were obtained by separate processing of slag and ore [13]. It has become possible to extract molybdenum from a collective concentrate obtained from ore and use slag flotation tailings containing 35-37% iron [10,12].…”
Section: Introductionmentioning
confidence: 99%